Follow the thing: data : contestations over data from the Global South - Akbari Kharazi, Azadeh (Antipode, 2020)
This research starts its journey from a video that failed to be published during the 2009 uprising in Iran. By following data outside the common trajectories of data circulation in the global North, ...
Gesehen am 14.01.2020